Whose quality is it anyway? Inhabiting the creative tension between presentational and participatory music. (1st September 2014) - Camlin, David A.
The complexity of identifying what constitutes quality in the field of Participatory Music is increased by contrasting it with its counterpart Presentational Music. Resorting to dichotomous positions – e.g. process vs product; access vs excellence; technical vs ethical – only helps to partially understand this complexity. In this article, I argue that applying a dialogic perspective of 'creative tension' to the continuums of practice between Presentational Music, Participatory Music and more socially or ethically engaged practices enables us to talk about issues of musical quality in participatory settings in a more meaningful and consistent way. This dialogic approach may also help to resolve similar dichotomies in broader Participatory Arts practice.